2005
DOI: 10.4141/p03-160
|View full text |Cite
|
Sign up to set email alerts
|

Tillage or no-tillage: Impact on mycorrhizae

Abstract: Kabir, Z. 2005. Tillage or no-tillage: Impact on mycorrhizae. Can. J. Plant Sci. 85: 23-29. Arbuscular mycorrhizal (AM) fungi are ubiquitous in agricultural soils. These fungi play important roles in plant nutrition and soil conservation. The persistence of AM fungi in ecosystems depends on the formation and survival of propagules (e.g., spore, hyphae and colonized roots). While spores are considered to be resistant structure that may be view as "long-term" propagules when viable host plants are not present, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
167
0
17

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(192 citation statements)
references
References 47 publications
8
167
0
17
Order By: Relevance
“…Alguns estudos demonstram os efeitos negativos do preparo do solo nos FMAs, sugerindo que isso possa promover a redução no rendimento da cultura posterior ao revolvimento do solo (COLOZZI-FILHO et al, 1999, KABIR, 2005, SOUZA et al, 2010. O preparo do solo é o mais direto e drástico estresse cultural que incide sobre a formação das micorrizas.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Alguns estudos demonstram os efeitos negativos do preparo do solo nos FMAs, sugerindo que isso possa promover a redução no rendimento da cultura posterior ao revolvimento do solo (COLOZZI-FILHO et al, 1999, KABIR, 2005, SOUZA et al, 2010. O preparo do solo é o mais direto e drástico estresse cultural que incide sobre a formação das micorrizas.…”
Section: Resultsunclassified
“…agrotec., Lavras, v. 35, n. 4, p. 701-709, jul./ago., 2011 A colonização micorrízica e comprimento de micélio extrarradicular foram afetados pelo sistema de manejo do solo (Tabela 2 e Figura 1), como já relatado por diversos autores (COLOZZI-FILHO et al, 1999;SANDERS, 1999;GOSS;VARENNES, 2002;KABIR, 2005;CASTILHO et al, 2006) Tabela 5 -Teste de comparação de médias dos componentes principais padronizados, entre as associações micorrízicas arbusculares analisados no primeiro eixo (PCA 1 ) e no segundo eixo (PCA 2 ), na cultura de soja, nos diferentes sistemas de manejo e calagem do solo, na região de Guarapuava, PR, janeiro de 2006. Primeira coleta, média de 3 repetições.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Spores are considered to be "long-term" propagules (Kabir 2005), mainly because it would take longer for spores to germinate and for the hypha to make contact with roots as opposed to runner hyphae infection from well developed extraradical mycelium (Klironomos and Hart 2002). Evans and Miller (1990) demonstrated that disruption of the hyphal network was directly responsible for much of the effect of soil disturbance on mycorrhizal colonization, leading to differences in AM colonization of almost 50% in pot trials and Brito et al (2006), under field conditions, reported 20% differences in AM colonization of wheat.…”
Section: Soil Disturbancementioning
confidence: 99%